A Nationwide Survey of Hepatitis E Virus Infection and Chronic Hepatitis in Heart and Kidney Transplant Recipients in Japan. Issue 2 (February 2020) - Owada, Yohei; Oshiro, Yukio; Inagaki, Yuki; Harada, Hiroshi; Fujiyama, Nobuhiro; Kawagishi, Naoki; Yagisawa, Takashi; Usui, Joichi; Akutsu, Naotake; Itabashi, Yoshihiro; Saito, Kazuhide; Watarai, Yoshihiko; et al.
Abstract : Background: Recently, chronic hepatitis E has been reported in solid organ transplant (SOT) recipients in European countries. Previously, we clarified the prevalence of hepatitis E virus (HEV) infection in Japanese liver transplant recipients and identified 2 chronic hepatitis E patients infected by blood transfusion. However, the rate of HEV infection in recipients of SOTs other than liver in Japan remains unclear, so we conducted a nationwide survey to clarify the prevalence of chronic HEV infection in Japanese heart and kidney transplant recipients. Methods: A total of 99 heart and 2526 kidney transplant recipients in 17 hospitals in Japan were examined for the presence of the IgG class of anti-HEV antibodies as well as for serum HEV RNA. Results: The prevalence of anti-HEV IgG among heart and kidney transplant recipients was 7.07% (7/99) and 4.08% (103/2526), respectively. One heart transplant patient (1.01%) and 11 kidney transplant patients (0.44%) were found to be positive for HEV RNA. The HEV isolates from all viremic patients were typed as genotype 3. Four patients developed chronic hepatitis E after transplantation. Three patients were treated with ribavirin; their liver enzymes normalized, and HEV RNA became negative immediately. Sustained virologic response was achieved in all cases. Conclusions: This is the first nationwide survey of HEV infection in Japanese heart and kidney transplant recipients. The prevalence of anti-HEV IgG and HEV RNA in heart and kidney transplant recipients in Japan was lower than that in European countries. Of note, 42% of viremic transplant patients developed chronic hepatitis.